Age and productivity: Human capital accumulation and depreciation - Anna Ruzik-Sierdzinska; Maciej Lis; Monika Potoczna; Michele Belloni; Claudia Villosio (Center for Social and Economic Research (CASE), 2013)
This NEUJOBS research report focuses on links between age, productivity and lifelong learning. Various data sources (EU-SILC, LFS, Structure of Earnings Survey, SHARE, ELSA, SHARELIFE) and methodological approaches were used in this report. Our analysis identifies clusters of countries with common characteristics of age-earnings profiles (for certain groups of employees) and allows for an explanation of those differences. Some differences can be attributed to the share of sectors, education types, and occupations in country-specific employment. Others are due to labour market institutions and the (dis)incentives to work at older ages provided by social security systems. Additionally, the dynamics of earnings after age 50 differ less between educational and occupational groups than at earlier ages. We show that the dynamics of average wages are strongly influenced by the timing of entering and leaving labour market. An estimation of the impact of LLL on productivity (measured by earnings) at older ages shows that for employees aged 50+, participation in training increases wages in the short-term.
Keywords: J24; J31; 330; Productivity; Age-Earning Profiles; Lifelong Learning